(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Thanks to multi-material Additive manufacturing (AM), it is nowadays possible to mimic the mechanical behavior of complex biological soft tissues. This enables, e.g., to experiment with novel implantable devices or surgical procedures in a non-risk setting. In a recent work [1], the authors considered four bio-inspired patterns: Tendon-Like (TL), Tendon-Mimic (TM), Bamboo-Like (BL), and Helix-Bamboo (HB). Multi-material dog-bone specimens (designed accordingly to ASTM Standard D638, Type IV shape) were produced with a Stratasys® J750™ Digital Anatomy 3D Printer (DAP) combining the Agilus30™ photopolymer at different Shore A hardness levels in several configurations. These included different matrix-to-fiber ratios, with the internal fibers arranged as complex layered structures (up to three layers). In total, 44 different variants, fully detailed in [1], were considered. The properties of these specimens were then assessed under uniaxial Ultimate Tensile Strength (UTS) tests, performed at the Laboratory of Bio-inspired Nanomechanics of Politecnico di Torino. An MTS Insight® Electromechanical Testing System specifically intended to characterize biological and bioinspired materials and Digital Image Correlation (DIC) were used to accurately quantify the specimens’ mechanical behavior in a non-contact fashion. The results – in terms of stress-strain curves, tensile strength at break, maximum strain at break, and modulus of elasticity – were then compared to the values of the equivalent base PolyJet materials. These comparisons showed that several patterns improved the mechanical response of the specimen with respect to their mono-material counterparts. For instance, at least one variant per each of the four classes (TL, TM, BL, and HB) returned a higher total deformation for comparable tensile strength. Thus, this work highlighted the potentialities of multi-material AM to integrate different hierarchical and complex shapes into single specimens. This enabling technology will play a decisive role in future biomedical applications, especially for repairing soft tissue (e.g., tendons and ligaments).